The Dark Side of Marketing Online Concert Tickets: A Mixed Methods Approach in the Framework of Consumer Protection - A.A Made Indra Wijaya Kusuma; I Nyoman Wahyu Ariartha; Kadek Riyan Putra Richadinata; Ketut Winda Pratiwi (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to analyze the influence of scarcity buying on immediate buying behavior through the mediation of Fear of Missing Out (FOMO) in online concert ticket consumers from a consumer protection perspective. The study used a mixed methods approach with a sequential explanatory design, combining quantitative and qualitative methods. Quantitative data were obtained by distributing questionnaires to 105 respondents who had purchased concert tickets online, then analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Meanwhile, qualitative data were obtained through in-depth interviews to strengthen the interpretation of empirical results related to digital marketing practices and consumer protection. The results showed that scarcity buying had a positive and significant effect on FOMO and immediate buying behavior. In addition, FOMO was also proven to have a positive effect on immediate buying behavior and was able to mediate the relationship between scarcity buying and immediate buying behavior. These findings indicate that scarcity-based marketing strategies can create psychological pressure that encourages consumers to make quick and impulsive purchases. From a consumer protection perspective, digital marketing practices such as countdown timers, limited stock, and real-time purchase notifications have the potential to create psychological manipulation if not accompanied by adequate information transparency. Therefore, it is necessary to strengthen regulations and supervision of digital marketing practices to ensure that consumer rights remain protected in the digital economy era.